Upaya Pencegahan Demam Berdarah Dengue melalui Edukasi Pemberantasan Sarang Nyamuk dengan Langkah 3M Plus - Tyagita Widya Sari; Nurmaliza Hasan; Retno Putri; Imelda Fitri; Nurul Aiyuda (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. DHF always increases at the start of every rainy season and causes Extraordinary Events (KLB) in several regions in Indonesia, including Riau Province. Eradicating dengue fever should prioritize prevention efforts by carrying out 3M Plus Mosquito Nest Eradication on an ongoing basis rather than focused fogging actions which are more frequently implemented nowadays. The aim of this service activity is to provide education on the 3M Plus Mosquito Nests Eradication so that it is hoped that it can increase knowledge and attitudes about dengue prevention behavior in children assisted by the As-Salaam Orphanage Pekanbaru City. Knowledge and attitudes about dengue prevention behavior are one of the factors that influence dengue prevention behavior in everyday life. Delivery of health material using the Leaflet tool was carried out by the head of the lecturer service team, while filling out the knowledge questionnaire about dengue prevention before and after health education, as well as documentation was carried out by members of the lecturer service team and students. The service activities lasted for ± 60 minutes and were attended by 13 children assisted by the orphanage. Descriptively, there is an increase in the knowledge of target children about dengue prevention, but this cannot be proven statistically. Health assistance efforts are sufficient to achieve goals, as shown by changes in results on the pretest and posttest questionnaires, but improvements need to be made in subsequent service activities, by combining health education methods with other relevant service methods.